Synthesis, Characterization and Antioxidant Studies on 4-Phenyl-1,3,5-triazine-2,6-diamine Schiff Bases and Their Nickel(II), Copper(II) and Zinc(II) Complexes - Ali, Abdulaziz; Abdullah, Norbani; Jamil Maah, Mohd (Asian Journal of Chemistry, 2013)
The synthesis, characterization, thermogravimetric and antioxidant activity of Schiff bases derived from 4-phenyl-1,3,5-triazine-2,6-diamine and 3,5-di-tert-butylsalicyladehyde (H2L) with their nickel(II), copper(II) and zinc(II) complexes are reported. The structures of the Schiff bases and the metal complexes wer characterized by elemental analyses (CHN), Fourier transform infrared spectroscopy (FT-IR) and ultraviolet-visible spectroscopy (UV-VIS). Additionaly, 1H- and 13C-nuclear magnetic resonance spectroscopy (NMR) were recorded for the Schiff bases, while thermogravimetric analysis was recorded for the complexes. Spectral studies reveal that the ligands were acting as tetradentate chelating agents and coordinated to the metal center via deprotonated phenolate oxygen and azomethine nitrogen atoms in a 1:1 ligand to metal ratio. The antioxidant activities of the ligand and the metal complexes were examined using the DPPH radical scavenging method. The results show that the ligand exhibit higher radical scavenging ability than the metal complexes.